Analisis Pemberdayaan Kelompok Tani Padi Sawah untuk Mendukung Kemandirian Pangan di Desa Bongohulawa Kecamatan Tilongkabila Kabupaten Bone Bolango - Wahab, Wanti A.; Rauf, Asda; Saleh, Yanti (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
This study aims to analyze the empowerment of rice farmer groups towards food independence in Bongohulawa Village, Tilongkabila District, Bone Bolango Regency. The main problems faced by farmers are limited business capital, access to financial institutions, so the role of institutions and microfinance institutions is needed in strengthening farming businesses. The study was conducted in January–March 2025 using a quantitative descriptive method. The sampling technique was carried out purposively with a total of 48 farmers as respondents, while data were obtained through observation, interviews, questionnaires, and documentation studies. Data analysis used simple linear regression analysis, t-test, f-test, and determination. The results showed that farmer group empowerment had a direct effect on food independence of 0.708. In addition, this research model explained 49.9% of the variation in food independence, while 50.1% was influenced by other factors outside the model. These findings confirm that collaboration between farmer groups is very important in supporting sustainable food independence.